2010
DOI: 10.1007/s10753-010-9261-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N-Acetylcysteine and Fructose-1,6-Bisphosphate in the Treatment of Experimental Sepsis

Abstract: Sepsis is a syndrome caused by uncontrolled systemic inflammatory response of the individual, which represents a serious epidemiological problem worldwide. The aim of this study was to investigate the effect of N-acetylcysteine (NAC) and fructose-1,6-bisphosphate (FBP) in the treatment of experimental sepsis. We used rats that were divided into five experimental groups: normal control (not induced), septic control (induced using a capsule with non sterile fecal content and Escherichia coli), treated with FBP (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 49 publications
2
7
0
Order By: Relevance
“…Previous studies in vivo of our group showed a reduction in mortality of animals subjected to experimental sepsis when treated with FBP (24) and NAC (21) , confirming an important role of both drugs in the treatment of sepsis. On the other hand, when rats were treated with combination of NAC and FBP, there was not improvement of the picture (21) .…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Previous studies in vivo of our group showed a reduction in mortality of animals subjected to experimental sepsis when treated with FBP (24) and NAC (21) , confirming an important role of both drugs in the treatment of sepsis. On the other hand, when rats were treated with combination of NAC and FBP, there was not improvement of the picture (21) .…”
Section: Discussionsupporting
confidence: 76%
“…On the other hand, when rats were treated with combination of NAC and FBP, there was not improvement of the picture (21) . Extensive evidence in the literature demonstrates a correlation between the increased proinflammatory cytokines production and the sepsis mortality rate, both in humans and experimental models, being the IL-1 and IL-6 cytokines suggested to play a key role.…”
Section: Discussionmentioning
confidence: 86%
“…Animal experiments have confirmed that N-acetylcysteine can reduce oxidative stress damage and the release of inflammatory mediators, which is beneficial to sepsis recovery [ 22 , 23 ]. Other experimental studies have shown that acetylcysteine can reduce organ injury [ 24 ] and improve survival [ 25 ]. The role of cysteine in the treatment of sepsis has also been confirmed in clinical trials [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This seems to be critical for the resolution of the bloodstream infection, since the lowest counts of platelets correlate with higher mortality rates (that occur within the first 48 h after induction of the infectious process). The role of FBP on platelets has been recently reported, being an important platelet aggregation inhibitor [22]. The inhibition of the platelet aggregation can be very important since this can improve the tissue perfusion that is harmed in the septic shock for the formation of clots [23].…”
Section: Discussionmentioning
confidence: 99%